1968
DOI: 10.1136/jcp.21.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of plasma zinc

Abstract: Zinc is an essential trace element. Previous methods of measuring zinc in clinical material have been difficult and reported findings must be treated with caution. Using atomic absorption spectroscopy it has been established that plasma zinc is one of the most uniform biochemical characteristics of normal adult blood. Sex and age differences in adult life are insignificant. Increased metabolic activity, on the other hand, induces a marked, immediate fall in plasma zinc level. The possible implications of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
2
5

Year Published

1970
1970
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(62 citation statements)
references
References 15 publications
4
51
2
5
Order By: Relevance
“…The tumour itself is probably not the source of the serum zinc as the levels are low. Similar values have been reported in hepatic metastases (Olson et al, 1958) which are not associated with raised serum levels (Vikbladh, 1951;Wolff, 1956;Davies, Musa and Dormandy, 1968).…”
Section: Discussionsupporting
confidence: 86%
“…The tumour itself is probably not the source of the serum zinc as the levels are low. Similar values have been reported in hepatic metastases (Olson et al, 1958) which are not associated with raised serum levels (Vikbladh, 1951;Wolff, 1956;Davies, Musa and Dormandy, 1968).…”
Section: Discussionsupporting
confidence: 86%
“…Zn 2ϩ titration against the HRPII effect showed that Zn 2ϩ interacts with HRPII with a K d of approximately 7M ( Figure 4B), which is around the physiologic concentration of Zn 2ϩ . 36 Data for the titration of HRPII at fixed AT-heparin for the inhibition of FXa and thrombin are presented in Figure 5. In the presence of Ca 2ϩ and Zn 2ϩ , the apparent IC 50 value for the HRPII neutralization of FXa inhibition by AT-heparin is approximately 30nM ( Figure 5A).…”
mentioning
confidence: 99%
“…Others (Davies et al, 1968;Davies 1972) Zinc plays an important role in nucleic acid and protein synthesis (Vallee, 1977) and tumour growth is retarded in zincdeficient rats (De Wys et al, 1970 (Schwartz et al, 1974 (Smith et al, 1973) and an effect of malnutrition on RBP synthesis cannot altogether be excluded. Against this explanation, however, is the finding of normal plasma protein levels in the lung-cancer patients.…”
mentioning
confidence: 99%